(untitled) (International Journal of Graphic Design, 2025)
Scientific search systems increasingly provide ranked documents, passages, and automated summaries, yet users must still determine whether retrieved evidence supports a claim, whether the presented information is sufficient for inspection, and why a result is highly ranked. This paper proposes an evidence-card UI/UX framework for scientific search that transforms retrieved articles into structured evidence cards containing a claim anchor, extractive evidence summary, support/refute/insufficient badge, confidence cue, citation cue, ranking rationale, and expandable source text. The framework is designed as a visual communication layer for retrieval transparency and evidence inspection rather than as a new claim-verification model or a live LLM system. Evaluation was conducted using the BEIR SciFact retrieval benchmark, the original SciFact train/dev datasets, and a SciFact-Open candidate-pool stress test. On the 300-query BEIR SciFact test set, the BM25-dominant hybrid baseline achieved nDCG@10 = 0.6667 and Recall@10 = 0.7858, while the proposed evidence-card pipeline achieved nDCG@10 = 0.6621 and Recall@10 = 0.7763. On the SciFact dev set, gold evidence appeared within the top three evidence-card candidates for 84.6% of evidence-bearing claims, and selected rationale sentences matched gold rationale annotations for 44.0% of gold evidence-document pairs. Interface-level analysis showed that the proposed card design increased the evidence visibility index from 0.2643 to 0.5920 and reduced the estimated first-pass scan-burden proxy from 115.50 to 84.08 seconds. These results suggest that evidence cards improve transparency by making relevance, uncertainty, confidence, and ranking rationale visible while preserving access to source evidence.